2018
DOI: 10.1161/jaha.118.010140
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Factors of Migraine in Patients With Spontaneous Coronary Artery Dissection

Abstract: Background Spontaneous coronary artery dissection (SCAD) is a cause of acute coronary syndrome predominantly in women without usual cardiovascular risk factors. Many have a history of migraine headaches, but this association is poorly understood. This study aimed to determine migraine prevalence among SCAD patients and assess differences in clinical factors based on migraine history. Methods and Results A cohort study was conducted using the Mayo Clinic SCAD “Virtual” M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 70 publications
3
76
0
1
Order By: Relevance
“…In addition to biomarkers of endothelial activation, procoagulable factors associated with migraine include thrombocytosis, polycythemia, antiphospholipid antibodies, and high estrogen states (pregnancy, CHC use) 151,152 . MWA has been associated with VTE risk in 2 prospective studies with the association ranging from 1.6 to 2.4‐fold 36,147 . In the Danish study, with a median age of 35 years, VTE was also associated with MWoA 36 .…”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 96%
See 1 more Smart Citation
“…In addition to biomarkers of endothelial activation, procoagulable factors associated with migraine include thrombocytosis, polycythemia, antiphospholipid antibodies, and high estrogen states (pregnancy, CHC use) 151,152 . MWA has been associated with VTE risk in 2 prospective studies with the association ranging from 1.6 to 2.4‐fold 36,147 . In the Danish study, with a median age of 35 years, VTE was also associated with MWoA 36 .…”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 96%
“…Migraine may also be associated with spontaneous coronary artery dissection (SCAD), a rare cause of MI. A recent multicenter cohort study found that 42% of women with SCAD had migraine, almost twice the rate in historical controls 147 …”
Section: Potential Mechanisms Of Migraine‐related Strokementioning
confidence: 99%
“…Women with SCAD and migraine history report more chest pain, depression, anxiety, and concern for recurrent SCAD than other SCAD patients. 22 Avoidance of medications with vasoconstrictive properties, such as triptans, is generally advised. β-Blockers can be considered as a preventive strategy.…”
Section: Outpatient Carementioning
confidence: 99%
“…FMD, a noninflammatory, nonatherosclerotic arteriopathy, is the most common vascular abnormality . More recently, in a Mayo Clinic series of 586 SCAD patients consisting primarily of women, there was a 40% lifetime and 27% 1‐year prevalence of migraine . Those with migraines reported more anxiety, depression, chest pain, and concern for future SCAD events.…”
Section: Associated Conditions and Risksmentioning
confidence: 99%
“… 7 Approximately one-third of patients have a history of hypertension. 8 , 9 Most patients have abnormalities in the peripheral arteries, such as fibromuscular dysplasia (FMD), aneurysms, and dissections. 1 , 10 , 11 , 12 , 13 Only a small proportion of patients have an inherited connective tissue disease (5%-8%) 14 , 15 or family members with SCAD (1%).…”
Section: Introductionmentioning
confidence: 99%